Acute weight gain and its relationship to success in high school wrestlers - Wroble, R. R.; Moxley, D. P. (Medicine & Science in Sports & Exercise, 1998)
The purpose of this study was to investigate 1. the extent of weight gain by high school wrestlers between an evening weigh-in and the first round of wrestling the next morning and 2. the relationship between weight gain and wrestling success. Result: The difference in weigt gain (WG) and relative weight gain ( RWG) between winners and losers was significant (P < 0.05). In 74 of the 130 bouts (57%), the heavier wrestler was successful.